Clinical features and long-term outcomes of interstitial lung disease with anti-neutrophil cytoplasmic antibody - Sun, Xin; Peng, Min; Zhang, Ting; Li, Zongru; Song, Lan; Li, Mengtao; Shi, Juhong (BMC pulmonary medicine, 2021)
Patients with interstitial lung disease (ILD) are occasionally positive for anti-neutrophil cytoplasmic antibodies (ANCAs). Differences between ILDs secondary to microscopic polyangiitis (MPA) and isolated ANCA-positive idiopathic interstitial pneumonia (IIP) remain unclear. The aim of this study was to explore the differences in clinical features and outcomes between MPA-associated ILDs and isolated ANCA-positive IIPs. We reviewed 1338 ILDs patients with available ANCA results and retrospectively analysed 80 patients who were ANCA-positive. MPA-associated ILDs (MPA-ILDs group) and isolated ANCA-positive IIPs (ANCA-IIPs group) were compared. Among 80 patients with ANCA-positive ILDs, 31 (38.75%) had MPA-ILDs, and 49 (61.25%) had isolated ANCA-positive IIPs. Compared with ANCA-IIPs group, patients in MPA-ILDs group had a higher proportion of fever (p = 0.006) and higher neutrophil count (p = 0.011), erythrocyte sedimentation rate (ESR) (p < 0.001) and C-reactive protein (CRP) (p = 0.005). Multivariable analysis showed that ESR level was an independent risk factor for mortality in all 80 ANCA-positive ILDs patients (HR 1.028, p = 0.001). Survival in MPA-ILDs group was lower than that in ANCA-IIPs group, and further stratified analysis revealed that ANCA-IIPs patients with elevated ESR or CRP had a worse prognosis than those with normal inflammation markers, with 5-year cumulative survival rates of 60.00%, 86.90% and 100.00% in MPA-ILDs and ANCA-IIPs with and without elevated inflammation markers, respectively. Among patients with ANCA-positive ILDs, the prognoses of ANCA-IIPs with normal inflammation markers, ANCA-IIPs with elevated inflammation markers and MPA-ILDs were sequentially poorer. Therefore, stratified treatment should be considered in the management of ILDs patients positive for ANCAs.